Constitutionalism and democratic transitions - Federico, Veronica (2006)
The book - as the outcome of a research performed by the University of Florence and the United States Institute of Peace of Washington - explores the role of law in the process of democratic transition in South Africa. More specifically it emphasize how constitutional law may contribute to "civilize" apparently unreconcilable conflicts, a part from laying down the foundations of the new legal order and institutions.